Factors affecting the filter paper method for total and matric suction measurements - Leong, Eng Choon (2011)
The filter paper method is used as an indirect means of measuring soil suctions. The advantages of the method include its simplicity, its low cost, and its ability to measure a wide range of suctions. The filter paper method has also been used in the field to measure soil suctions. However, the simplicity of the filter paper method has led to an inadequate understanding of the method and, therefore, improper usage. Recent findings have highlighted the need for more precautions in the use of the filter paper method for suction measurements. This paper presents a literature review of the factors affecting the accuracy of the filter paper method and identifies gaps in the current knowledge of the method. An experimental study was also conducted to clarify some of the factors affecting the response of the two most commonly used filter papers for suction measurements. Whatman No. 42 and Schleicher and Schuell No. 589. Calibration curves of the filter papers show that the water content-suction relationships are different for total and matric suctions. The total suction calibration curve is not very sensitive to applied suctions less than 1000 kPa. The calibration curves obtained for total suction are different from those recommended in ASTM D 5298-94, suggesting that the ASTM D 5298-94 equations should not be used for total suction. Instead of existing bilinear equations, new equations are proposed to describe the total and matric suction calibration curves. All the equations were evaluated using the filter paper method to measure the suction of soil specimens of known matric suctions.